2018
DOI: 10.4236/wjcs.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive-Ventilation-Renal Score Predicts Cardiac Care Unit Length of Stay in Patients Undergoing Re-Entry Sternotomy: A Derivation Study

Abstract: Background: The vasoactive-ventilation-renal (VVR) score includes pulmonary and renal dysfunctions not previously addressed by the vasoactive inotrope score (VIS) and may be a better predictor of cardiac care unit (CCU) length of stay (LOS) in patients undergoing re-entry sternotomy (defined as no earlier than 30 days after previous sternotomy) for congenital heart disease (CHD). Methods: Patients undergoing re-entry sternotomy for CHD from August 1, 2009 to June 30, 2016 were studied retrospectively. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There has been a variable cutoff value for VVR scores in previous studies in order to predict adverse outcomes. 10,12,16,17 Miletic et al established the cutoff value of peak VVR score to be 22.5 at 48 hours in their pediatric population. 10,11 While Scherer et al reported a cutoff value of 25 for the peak VVR score at 12 hours in their population that included both children and adults with CHD, Garcia et al described a lower VIS cutoff value in an adolescent population with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a variable cutoff value for VVR scores in previous studies in order to predict adverse outcomes. 10,12,16,17 Miletic et al established the cutoff value of peak VVR score to be 22.5 at 48 hours in their pediatric population. 10,11 While Scherer et al reported a cutoff value of 25 for the peak VVR score at 12 hours in their population that included both children and adults with CHD, Garcia et al described a lower VIS cutoff value in an adolescent population with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The VVR score is a simple, cost-effective multi-organ scoring system that can be used at the bedside or for research purposes to predict patients' prognosis following cardiac surgery. The VVR score at 12 and 48 h shows the most promise and re ects postoperative outcomes, such as length of stay (LOS), intensive care unit (ICU) stay, use of mechanical ventilation, need for inotropic and vasoactive treatment, and use of dual chest tube drainage [1,3,4]. The VVR score is more accurate in predicting the severity of postoperative diseases as well as short-term outcomes, including LOS and mechanical ventilation duration, compared with single system scoring methods, such as the Vasoactive-Ionotropic Score and the peak postoperative lactate [3].…”
Section: The Vasoactive-ventilation-renal Scoring Systemmentioning
confidence: 99%
“…Miletic et al recently developed a new score, the vasoactive-ventilation-renal (VVR) score, to address the inability of previous scores to reflect multiorgan failure, especially concerning pulmonary and renal systems ( 11 ). The VVR score has been found to be easy to use, straightforward to calculate, and a strong predictor of postcardiac surgery outcomes ( 12 ). The VVR score was subsequently validated to predict postoperative outcomes and mortality in the pediatric postoperative cardiac surgical population ( 11 , 13 – 15 ).…”
Section: Introductionmentioning
confidence: 99%